2023
DOI: 10.2186/jpr.jpr_d_22_00255
|View full text |Cite
|
Sign up to set email alerts
|

Maternal chewing alleviates prenatal stress-related neuroinflammation mediated by microglia in the hippocampus of the mouse offspring

Abstract: Prenatal stress affects the hippocampal structure and function in pups. Maternal chewing ameliorates hippocampus-dependent cognitive impairments induced by prenatal stress. In this study, we investigated hippocampal microglia-mediated neuroinflammation in pups of dams exposed to prenatal stress with or without chewing during gestation. Methods: Pregnant mice were randomly assigned to control, stress, and stress/chewing groups. Stress and stress/chewing animals were subjected to restraint stress for 45 min thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Additionally, despite subjecting the dams to prenatal stress 3 times daily for eleven days, the dams may have received comparatively less stress through behavioral coping skills during the gestational restraint stress procedure such as maternal chewing behavior (Hisada et al, 2023). However, we have shown that prenatal stress impacts the behavioral outcomes in Swiss Webster mice, indicating that this prenatal stress exposure is successful in another strain of mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, despite subjecting the dams to prenatal stress 3 times daily for eleven days, the dams may have received comparatively less stress through behavioral coping skills during the gestational restraint stress procedure such as maternal chewing behavior (Hisada et al, 2023). However, we have shown that prenatal stress impacts the behavioral outcomes in Swiss Webster mice, indicating that this prenatal stress exposure is successful in another strain of mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, despite subjecting the dams to prenatal stress 3 times daily for eleven days, the dams may have received comparatively less stress through behavioral coping skills during the gestational restraint stress procedure such as maternal chewing behavior (Hisada et al, 2023).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Maternal exposure to LPS during the late stages of gestation led to an increase in inflammatory cytokine concentrations through a series of downstream signaling pathways. These cytokines could cross the maternalplacenta barrier and induce an inflammatory response in the fetus (Hisada et al, 2023). Previous studies have demonstrated that maternal exposure to LPS induced the activation of microglia/ macrophages and stimulated the release of inflammatory cytokines such as IL-1β, IL-6, and TNF-α in the brains of offspring (Dominguez Rubio et al, 2017;Rahimi et al, 2020).…”
Section: Resveratrol Improved the Response To Inflammation Induced By...mentioning
confidence: 99%